Forgotten solidarities in the Atelier Populaire posters. Issue 1 (1st July 2019) - Memou, Antigoni
AbstractThis article examines some of the 'forgotten' posters of the Atelier Populaire, which were collectively produced by artists, workers, students and activists among others in the occupied Beaux-Arts school during the events of May '68. The article argues that alternative visual narratives are to be discovered in these posters, which break away from the representations of the events as youth revolt and the geographical reduction of the events to Paris and the Cartier Latin. Looking at them anew allows us to rediscover the unique solidarity among students, workers, farmers, the migrant workers and the unemployed, and to decipher the anti-capitalist character of the movement and its global dimensions.